Protection For Business Actors Due To Unilateral Cancellation From Consumers In The Pre-Order Method Of Buying And Selling Online (A Study In Islamic Law) - Rahmadi Indra Tektona (Journal of Nusantara Economy, 2023)
The principle adopted in buying and selling online is an attitude of trust. After mutual trust, there will be an agreement between the seller and the buyer, then both parties exchange information to follow up on the sale and purchase transaction. Islam has clear rules regarding buying and selling transactions as a basis for business transactions for Muslims The existence of a pre-order trading system or ordering goods before the goods are available has become a significant trend in online commerce today. In the context of pre-orders, business actors risk unilateral cancellation from consumers after they order goods. This can be detrimental to business actors, especially if they have ordered or produced goods based on the number of orders. Islamic law emphasizes the concept of justice in all aspects of life, including in business transactions. Therefore, protection for business actors must also reflect fairness for both parties. From the background above, the author takes the formulation of the problem of how to protect business actors due to unilateral cancellation from consumers in the pre-order method of buying and selling online (a study in Islamic law).